FAKTOR-FAKTOR YANG MEMENGARUHI INTEGRITAS LAPORAN KEUANGAN - Laila Hidayah; Fitri Fauziah (Universitas Slamet Riyadi, 2022)
The aims of his study was to determine the effect of audit quality, company size, institutional ownership, managerial ownership on the integrity of financial statements in various industrial sector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. Research sample in this study are various industrial sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. Sample selection using purposive sampling method. The data analysis technique used multiple linear regression analysis. Based on statistical analysis, it can be concluded that audit quality and company size has a negative effect on the integrity of financial statements. Institutional ownership and managerial share ownership has no effect on the integrity of financial statements.